2006
DOI: 10.1007/s00382-006-0114-z
|View full text |Cite
|
Sign up to set email alerts
|

Asian summer monsoon anomalies induced by aerosol direct forcing: the role of the Tibetan Plateau

Abstract: In this paper we present results of a numerical study using the NASA finite-volume GCM to elucidate a plausible mechanism for aerosol impact on the Asian summer monsoon involving interaction with physical processes over the Tibetan Plateau. .During the pre-monsoon season of March-April, dusts from the deserts of western China, Afghanistan/Pakistan, and the Middle East are transported into and stacked up against the northern and southern slopes of the Tibetan Plateau. The absorption of solar radiation by dust h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
716
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 942 publications
(761 citation statements)
references
References 21 publications
42
716
2
1
Order By: Relevance
“…However, the impact of aerosols on monsoon rainfall in a coupled model was found to be different from that in uncoupled models with specified SSTs (Chung et al 2002;Menon et al 2002;Lau et al 2006) as a result of the response of SSTs themselves to aerosol forcing. Ramanathan et al (2005), using a coupled ocean-atmosphere model with aerosols over South Asia prescribed according to measurements, found that, while aerosol absorption of solar radiation and consequent heating of the atmosphere leads to enhanced upward motion over India during winter, it also leads to a weakening of the monsoon circulation and a reduction of rainfall over India during summer.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…However, the impact of aerosols on monsoon rainfall in a coupled model was found to be different from that in uncoupled models with specified SSTs (Chung et al 2002;Menon et al 2002;Lau et al 2006) as a result of the response of SSTs themselves to aerosol forcing. Ramanathan et al (2005), using a coupled ocean-atmosphere model with aerosols over South Asia prescribed according to measurements, found that, while aerosol absorption of solar radiation and consequent heating of the atmosphere leads to enhanced upward motion over India during winter, it also leads to a weakening of the monsoon circulation and a reduction of rainfall over India during summer.…”
Section: Introductionmentioning
confidence: 90%
“…Absorbing aerosols have been shown to be influential in the context of long-term changes (or trends) in summer monsoon rainfall (e.g., Ramanathan et al 2005;Chung and Ramanathan 2006;Lau et al 2006;Meehl et al 2008) and its interannual variability (LK06). The summer season is particularly challenging because extensive cloudiness at this time brings the aerosol indirect effects into play in addition to the land and ocean surface-related feedbacks.…”
Section: Synopsis and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…The complex terrain and the amount and distribution of solar energy on the Qinghai-Tibet Plateau have significant influences on the Asian monsoon and the global climate changes (Bai and Xu, 2004;Lau et al, 2006). However, the atrocious geographical and natural conditions make it quite difficult for the scientists to carry out more and frequent solar radiation observations.…”
Section: Introductionmentioning
confidence: 99%